High Cancer Burden Among Antiretroviral Therapy Users in Malawi: A Record Linkage Study of Observational Human Immunodeficiency Virus Cohorts and Cancer Registry Data. (17th November 2018) - Horner, Marie-Josèphe; Chasimpha, Steady; Spoerri, Adrian; Edwards, Jessie; Bohlius, Julia; Tweya, Hannock; Tembo, Petros; Nkhambule, Franklin; Phiri, Eddie Moffo; Miller, William C; Malisita, Kennedy; Phiri, Sam; et al.
Abstract: Background: With antiretroviral therapy (ART), AIDS-defining cancer incidence has declined and non-AIDS–defining cancers (NADCs) are now more frequent among human immunodeficiency virus (HIV)–infected populations in high-income countries. In sub-Saharan Africa, limited epidemiological data describe cancer burden among ART users. Methods: We used probabilistic algorithms to link cases from the population-based cancer registry with electronic medical records supporting ART delivery in Malawi's 2 largest HIV cohorts from 2000–2010. Age-adjusted cancer incidence rates (IRs) and 95% confidence intervals were estimated by cancer site, early vs late incidence periods (4–24 and >24 months after ART start), and World Health Organization (WHO) stage among naive ART initiators enrolled for at least 90 days. Results: We identified 4346 cancers among 28 576 persons. Most people initiated ART at advanced WHO stages 3 or 4 (60%); 12% of patients had prevalent malignancies at ART initiation, which were predominantly AIDS-defining eligibility criteria for initiating ART. Kaposi sarcoma (KS) had the highest IR (634.7 per 100 000 person-years) followed by cervical cancer (36.6). KS incidence was highest during the early period 4–24 months after ART initiation. NADCs accounted for 6% of new cancers. Conclusions: Under historical ART guidelines, NADCs were observed at low rates and were eclipsed by high KS and cervical cancer burden. Cancer burden among Malawian ART users does not yet mirror that in high-income countries. Integrated cancer screening and management in HIV clinics, especially for KS and cervical cancer, remain important priorities in the current Malawi context. Abstract : In sub-Saharan Africa, limited epidemiological data describe cancer burden among antiretroviral therapy users. Integrated cancer screening and management in human immunodeficiency virus clinics, especially for Kaposi sarcoma and cervical cancer, remain important priorities in the current Malawi context.